Riviera. Season two [videorecording (DVD)] - Jordan, Neil, 1950-; Eshkeri, Ilan (Universal Pictures Home Entertainment, 2021)
Georgina is focused on trying to get away with murder as she gets to retain power within the Clios household and her position at the top of the elusive art world. The Clios family is still reeling from the devastation caused by Constantine's mysterious death, while Georgina continues her battle for dominance and control with Irina Clios and her children Christos and Adriana.